2019
DOI: 10.3122/jabfm.2019.03.180271
|View full text |Cite
|
Sign up to set email alerts
|

Does Ownership Make a Difference in Primary Care Practice?

Abstract: Purpose: We assessed differences in structural characteristics, quality improvement processes, and cardiovascular preventive care by ownership type among 989 small to medium primary care practices.Methods: This cross-sectional analysis used electronic health record and survey data collected between September 2015 and April 2017 as part of an evaluation of the EvidenceNOW: Advancing Heart Health in Primary Care Initiative by the Agency for Health Care Research and Quality. We compared physician-owned practices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…22 In fact, a prior study examining a national program to improve cardiovascular preventative care found that CHCs had considerably higher rates of participation in quality improvement initiatives compared with physicianowned practices. 23 Similarly, some evidence suggests that CHCs may be more likely to escalate care for chronic conditions, like uncontrolled hypertension, compared with private practices. 24 During the same time period as our study, there was a concerted national effort to reform healthcare delivery and certify FQHCs as patient-centered medical homes (PCMH).…”
Section: Discussionmentioning
confidence: 99%
“…22 In fact, a prior study examining a national program to improve cardiovascular preventative care found that CHCs had considerably higher rates of participation in quality improvement initiatives compared with physicianowned practices. 23 Similarly, some evidence suggests that CHCs may be more likely to escalate care for chronic conditions, like uncontrolled hypertension, compared with private practices. 24 During the same time period as our study, there was a concerted national effort to reform healthcare delivery and certify FQHCs as patient-centered medical homes (PCMH).…”
Section: Discussionmentioning
confidence: 99%
“…The funding agency specified the four targeted CQMs for all practices participating in the national EvidenceNOW initiative. 16 The CQMs for aspirin use, blood pressure control, cholesterol management, and smoking cessation aligned with the National Quality Forum We used all available data reported by practices by June 1, 2018, the end of the final quarter for required CQMs for the analysis reported here. Not all practices were able to report CQMs by this date.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The surveys were designed in collaboration with the national EvidenceNOW evaluation team. 15,16 One 48-item practice survey per practice was completed by a lead administrator and lead clinician to gather descriptive information at the practice and organizational level. The practice survey included the Change Process Capability Questionnaire, an assessment of quality improvement strategies.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] There is a growing literature that compares cost and quality of care between care provided by integrated providers and those provided by independent providers. Previous studies on this topic have used hospital-based quality data, 9 survey data, [10][11][12] data from selected organizations, 13 or claims data from the Medicare population 14 to investigate the impact of integration on quality of care. This study is one of the first to study the relationship between health system integration and primary care quality and cost of care using commercial claims data.…”
Section: Introductionmentioning
confidence: 99%